Influence Bystander Effect and Whistleblowing to Fraud Billing Receivables: (Empirical Study on Employees of PT Lotus Pradipta Mulia) - Amelia, Monica; Amna, Luke Suciyati (International Journal Of Education, Social Studies, And Management (IJESSM), 2025)
Receivables is element important in finance company, but fraud in the billing can become significant challenges. This study designed For to study to what extent does it influence bystander effect and whistleblowing to fraud billing receivables at PT Lotus Pradipta Mulia. With involving all over population company (32 people) as sample through method sample saturated, research that uses method multiple linear regression For measure data reliability, consistency instruments, as well as influence second variable to potential cheating. The test results prove that bystander effect own effect negative to fraud billing receivables, whereas whistleblowing give effect positive. The significance values for both variables are 0.035 and 0.037 (<0.05). Both variable This in a way simultaneous influential to fraud billing receivables, value significant 0.010 (<0.05).